2004
DOI: 10.1038/sj.gene.6364069
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression of pyruvate kinase deficiency and protection against malaria in a mouse model

Abstract: The recombinant congenic mouse strains AcB55 and AcB61 are extremely resistant to malaria (Plasmodium chabaudi AS) despite the presence of susceptibility alleles at the known Char1/Char2 resistance loci. Resistance in AcB55 and AcB61 is controlled by a locus on chromosome 3 (Char4) shown to be allelic with or tightly linked to a loss-of-function mutation in pyruvate kinase (Pklr). AcB55 and AcB61 show important splenomegaly prior to infection caused by the expansion of the red pulp, and display histological si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…42 The various cell populations were determined by singlecolor staining of the cells with fluorescein isothiocyanateor phytoerythrin-conjugated monoclonal antibodies against Mac-1 (CD11b, clone M1/70, rat IgG2b), Gr-1 (Ly-6G and Ly-6C, clone RB6-8C5, rat IgG2b), CD3e (clone 145-2C11, hamster IgG1), CD11c (clone HL3, hamster IgG1), CD49b/Pan-NK (clone DX5, rat IgM), I-A b (clone AF6-120.1, mouse (BALB/c) IgG2a) and IgM (clone R6-60.2, rat IgG2a). CD16/CD32 (clone 2.4G2, rat IgG2b) was used before staining to block the nonspecific binding by Fc receptors.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…42 The various cell populations were determined by singlecolor staining of the cells with fluorescein isothiocyanateor phytoerythrin-conjugated monoclonal antibodies against Mac-1 (CD11b, clone M1/70, rat IgG2b), Gr-1 (Ly-6G and Ly-6C, clone RB6-8C5, rat IgG2b), CD3e (clone 145-2C11, hamster IgG1), CD11c (clone HL3, hamster IgG1), CD49b/Pan-NK (clone DX5, rat IgM), I-A b (clone AF6-120.1, mouse (BALB/c) IgG2a) and IgM (clone R6-60.2, rat IgG2a). CD16/CD32 (clone 2.4G2, rat IgG2b) was used before staining to block the nonspecific binding by Fc receptors.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…in (Hernandez-Valladares et al, 2005)]. Using positional cloning, we have shown that the protective effect of the Char4 locus is caused by a loss-of-function mutation in the erythrocyte form of pyruvate kinase ( Pklr I90N ) (Min-Oo et al, 2003; Min-Oo et al, 2004). Likewise, we observed that homozygosity and heterozygosity for mutant alleles at the human PKLR gene also protect against Plasmodium falciparum malaria in erythrocytes ex vivo (Ayi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Splenomegaly was apparent and histological analysis revealed breakdown of normal splenic architecture and massive expansion of the red pulp in AcB62 (Figure 2a), all known consequences of PK deficiency. 11 Compared with A/J, AcB62 and AcB55 showed elevated spleen cell counts (twofold to fourfold increase; Figure 2b), and a higher fraction of CD71 þ /TER119 þ doubly positive erythroid precursors (Figure 2c). Owing to an RBC lysis step of spleen cell suspensions performed before labeling, the percentage of erythroid precursor cells is likely under-represented, but nevertheless indicates higher levels of erythroid progenitors in the PK mutant strains compared with A/J mice.…”
mentioning
confidence: 99%
“…These parameters suggest the presence of a slightly more severe anemia in AcB62 compared to that which we have reported earlier for AcB55 and AcB61. 11 Like AcB55, and as opposed to A/J controls, AcB62 mice show signs of compensatory erythropoietic activity in the spleen ( Figure 2) and liver (not shown). Splenomegaly was apparent and histological analysis revealed breakdown of normal splenic architecture and massive expansion of the red pulp in AcB62 (Figure 2a), all known consequences of PK deficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation